Immune-related adverse events on body CT in patients with small-cell lung cancer treated with immune-checkpoint inhibitors. Issue 132 (November 2020) - Park, Hyesun; Hatabu, Hiroto; Ricciuti, Biagio; Aijazi, Safiya J.; Awad, Mark M.; Nishino, Mizuki
Highlights: 36 % of SCLC patients treated with PD-1/PD-L1 inhibitors had irAE on body CT. Colitis and pneumonitis were the most common types of irAEs. Older age and the history of previous radiotherapy were associated with irAEs. Prior chest radiotherapy was a predictor of with pneumonitis or thyroiditis. The results call for awareness of risk factors and CT findings of irAEs in SCLC. Abstract: Purpose: Investigate the incidence and imaging characteristics of radiologically-evident immune-related adverse events (irAEs) on body CT in patients with small-cell lung cancer (SCLC) treated with immune-checkpoint inhibitors. Methods: The study included 53 patients with relapsed/refractory SCLC (27 men, 26 women) treated with PD-1/PD-L1 inhibitors alone or in combination with CTLA-4 inhibition, who had baseline and at least one follow-up body CT during therapy. Body CT scans were reviewed to detect and characterize organ-specific irAEs including thyroiditis, pneumonitis, hepatitis, pancreatitis, enteritis, and colitis. Results: Nineteen patients (36 %) developed radiologically-evident irAEs. The median time from therapy initiation to irAE onset was 7.1 weeks. Pneumonitis and colitis were most common, noted in 9 patients (17 %) each. Seven colitis cases demonstrated pancolitis, and two cases showed segmental colitis associated with diverticulosis. The common radiographic patterns of pneumonitis were acute interstitial pneumonia (AIP)/acute respiratory distress syndrome (ARDS) pattern (n = 4) and cryptogenic organizing pneumonia (COP) pattern (n = 3). Other irAEs included thyroiditis (n = 3), enteritis (n = 2), hepatitis (n = 1), and pancreatitis (n = 1). Older age (p = 0.03) and prior radiotherapy to any organ (p = 0.03) was associated with overall irAEs. Prior chest radiotherapy was significantly associated with pneumonitis or thyroiditis (p = 0.0004). Conclusion: Radiologically-evident irAEs were noted on body CT in 36 % of patients with SCLC treated with immune-checkpoint inhibitors. Colitis and pneumonitis were most common. Prior chest radiotherapy was a predictor of the development of both pneumonitis and thyroiditis. Awareness of risk factors and CT findings of irAEs is important for early detection and accurate diagnosis of potentially serious immunotherapy toxicities.